The Role of Multinational Enterprises in Achieving Sustainable Development - The Case of Huawei - Berning, Sue Claire (European Journal of Sustainable Development, 2019)
The aim of this paper is to investigate the relationship between business and sustainable development, particularly the role of multinational enterprises (MNEs) as possible driving force for achieving sustainability. By following an inductive case study approach and referring to the Sustainable Development Goals (SDGs) of the United Nations, the sustainable undertakings of the Chinese MNE Huawei are explored. Published data on Huawei’s website and online resources like annual reports, news announcements, sustainability and corporate social responsibility reports are used for this purpose. The main findings indicate that Huawei can promote sustainable development internationally on three different levels: (1) products/services, (2) business operations and (3) social contributions. Based on these findings, a systematic framework is derived to help illustrate possible and classify existing MNE’s sustainability activities, as well as the related main stakeholders. This paper is useful for scholars and practitioners alike as it shows the compatibility of success in business with sustainability, as well as the potential of MNEs to contribute to sustainable development. Keywords: Sustainable Development Goals, business, multinational enterprises, emerging markets